Enhancing Students’ Reading Comprehension through the Flipped Classroom Model at Junior High School - Rochma, Anis Fatur; Khoiriyah; Sulistyani (Proceeding International Conference on Education, 2025)
This research aims to examine the effect of Flipped Classroom Model in enhancing junior high school students' reading comprehension. This study uses a quantitative method with a quasi-experimental design. The population of this study is eighth grade of SMPN 1 Tarokan with a sample of two classes with a total of 64 students selected using purposive sampling technique. The experimental class used the Flipped Classroom Model, while the control class used traditional learning methods. The data were collected through multiple-choice tests given before and after the treatment. The results of data analysis showed a significant improvement in reading comprehension scores in the experimental class compared to the control class. The results of this research indicate that the Flipped Classroom model is effective in improving students' reading comprehension, especially in narrative texts. In addition, this model is also able to increase student engagement in the learning process. This study concludes that the Flipped Classroom Model is an innovative technology-based learning model that can be adopted in reading comprehension teaching at the junior high school level. This model is relevant to be applied in the context of modern education that requires technology integration to improve the quality of learning.